Exploring potential of goat based dairy farming in India and way forward - SINGH, M K; SINGH, S K; CHAUHAN, M S (The Indian Journal of Animal Sciences, 2023)
The aim of this review is to highlight the significance of goat milk along with potential and prospects of dairy goat development in the country. India occupies the first position in goat milk production in the world. In the last few years, commercial dairy goat production in India gained momentum due to spread of knowledge about therapeutic, nutraceutical and medicinal benefits of goat milk and its product, and their export potential. India possesses vast caprine resources with 37 goat breeds distributed in different bio-climates with varied nutritive value, however, some goat breeds native to north and north-western region namely Beetal, Jamunapari, Jakhrana, Surti and Zalawadi are considered as Indian dairy breed with 150 to 500 litre milk yields. The reported milk yield of Indian dairy goat is far below their potential, since they are primarily raised for mutton and also due to energy-deficient diet. Attempts so far made were scarce and limited for milk improvement of dairy goats and in creating infrastructure for goat milk processing and marketing. Use of potential sire/semen and infrastructural support for a secured market for goat milk and products is necessary to enhance dairy goat productivity and profitability. To cater the demand for goat milk in southern, eastern and hilly regions, suitable dairy breeds need to be developed along with increasing the genetic potential of existing breeds. Development of the goat dairy sector will require focused efforts to encourage entrepreneurship to set as many as possible commercial dairy farms by involving private sector through appropriate policy support and incentives.